Association of Health Literacy with Complementary and Alternative Medicine Use: A Cross-Sectional Study in Adult Primary Care Patients - Bains Sujeev S; Egede Leonard E (BMC, 2011)
Abstract Background In the United States, it is estimated that 40% of adults utilize complementary and alternative medicine (CAM) therapies. Recently, national surveys report that over 90 million adults have inadequate health literacy. To date, no study has assessed health literacy and its effect on CAM use. The primary objective of this study was to assess the relationship between health literacy and CAM use independent of educational attainment. Second objective was to evaluate the differential effect of health literacy on CAM use by race. Methods 351 patients were recruited from an outpatient primary care clinic. Validated surveys assessed CAM use (I-CAM-Q), health literacy (REALM-R), and demographic information. We compared demographics by health literacy (adequate vs. inadequate) and overall and individual CAM categories by health literacy using chi square statistics. We found a race by health literacy interaction and ran sequential logistic regression models stratified by race to test the association between health literacy and overall CAM use (Model 1), Model 1 + education (Model 2), and Model 2 + other demographic characteristics (Model 3). We reported the adjusted effect of health literacy on CAM use for both whites and African Americans separately. Results 75% of the participants had adequate literacy and 80% used CAM. CAM use differed by CAM category. Among whites, adequate health literacy was significantly associated with increased CAM use in both unadjusted (Model 1, OR 7.68; p = 0.001) and models adjusted for education (Model 2, OR 7.70; p = 0.002) and other sociodemographics (Model 3, OR 9.42; p = 0.01). Among African Americans, adequate health literacy was not associated with CAM use in any of the models. Conclusions We found a race by literacy interaction suggesting that the relationship between health literacy and CAM use differed significantly by race. Adequate health literacy among whites is associated with increased CAM use, but not associated with CAM use in African Americans.